Parvovirus B19 infection during pregnancy: a problem not only for the gynaecologist - Hermyt, Ewelina; Jęda-Golonka, Agnieszka; Zmarzły, Nikola; Szczepanek, Katarzyna; Stanienda-Sokół, Karolina; Mazurek, Urszula; Witek, Andrzej (Paediatrics and Family Medicine, 2019)
Parvovirus B19 (B19V), which belongs to the Parvoviridae family, is one of the smallest viruses causing infections in humans. It is estimated that approximately 60% of the population will have a parvovirus B19 infection at some point in their lives based on B19V-specific antibody detection rates. The frequency of infections increases with age. Asymptomatic B19V infections are relatively common both in adults and in children. Parvovirus B19 is an aetiological factor for numerous diseases such as, for example, arthritis, erythema infectiosum, gloves and socks syndrome or haematological disorders. B19V infection is particularly dangerous during pregnancy due to the risk of maternal-foetal transmission; the estimated risk of virus transmission during pregnancy is 17–33%. The majority of infected foetuses have a good prognosis and experiencing intrauterine infection does not result in permanent sequelae; however, B19V infection during pregnancy can cause spontaneous abortion, hydrops fetalis or intrauterine death, among others; there are also single cases reported of congenital defects in the foetuses. In every pregnant woman with a suspected parvovirus B19 infection, assay of virus-specific IgM and IgG antibodies should be performed. If primary B19V infection is detected in a pregnant patient, she should be referred to a referral centre and undergo close observation with periodic foetal ultrasound examination. Children who have a history of parvovirus B19 infection during foetal life require specialist follow-up after birth. To date no specific method for B19V infection treatment has been developed. In addition, there is no vaccine against this virus.